Hepatocellular carcinoma and macrophage interaction induced tumor immunosuppression via Treg requires TLR4 signaling - Yang, Jing (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigated the interaction between toll-like receptor 4 (TLR4)-activated hepatoma cells and macrophages in the induction of tumor-immune suppression mediated by CD4+CD25(high) family of transcription factor P3 (FOXP3) regulatory T cells (Tregs). METHODS: The proportion of FOXP3+ Tregs was identified in peripheral blood and tumor tissues of 60 hepatocellular carcinoma (HCC) patients. TLR4 expression was examined in tumor tissues and cell lines. The correlation was examined between FOXP3+ Tregs in peripheral blood and TLR4 expression of HCC tissues. Following activation of TLR4 in H22 murine hepatoma cells pre-incubated with lipopolysaccharide (LPS) and co-cultured with macrophage cell line RAW246.7, the synthesis of cytokines tumor necrosis factor-α, CCL22, and interleukin (IL)-10 by the two cell lines was detected and analyzed. RESULTS: FOXP3+ Tregs were enriched in tumor sites, and circulating FOXP3+ Tregs were increased in HCC patients in correlation with multiple tumor foci and up-regulated TLR4 expression in HCC tissues. Semi-quantitative analysis indicated that TLR4 was over-expressed in HCC compared with the matched normal tissues. Cell cultivation experiments indicated that the mRNAs of IL-10 and CCL22 were significantly up-regulated in the RAW246.7 cell line when co-cultured with LPS pre-incubated H22 cells. CONCLUSION: In hepatoma cell lines, TLR4 may indirectly facilitate the recruitment of Tregs to the tumor site and promote intrahepatic metastasis through its interaction with macrophages.